Investigation of the Relationship of Nesfatin-1, Adropin Levels and Claudin-2, Renalase Immunoreactivity with Kidney Function in an Experimental Hypertension Model - Aydin, Muhammed Ali; Aydogdu, Nurettin; Tastekin, Ebru; Firat, Nihayet; Yalcinkaya Yavuz, Ozlem (Puerto Rico Health Sciences Journal, 2024)
Objective: Hypertension is one of the cardiovascular diseases that causes the most mortality, and 95% of the causes are unknown. The aim of the study was to examine the possible correlation of nesfatin-1 levels, adropin levels, claudin-2 immunoreactivity (claudin-2 expression in the renal proximal tubule), and renalase immunoreactivity (renalase expression in the renal proximal tubule) with arterial blood pressure, kidney function, and kidney damage. Methods: Adult male Sprague Dawley rats were divided into control and hypertension groups (8 per group). Angiotensin II vehicle was given to the control group and angiotensin II (0.7 mg/kg/day) to the hypertension group, both via an osmotic mini pump for 7 days. The animals blood pressures were measured by tail cuff plethysmography on days 1, 3, 5, and 7. On day 7, 24-hour urine, blood, and tissues were collected from the rats. Results: In the hypertension group compared with the control group, there was an increase in systolic blood pressure levels after day 1. While claudin-2 immunoreactivity was reduced in the kidneys, renalase immunoreactivity was increased. There was a decrease in creatinine clearance and an increase in fractional potassium excretion (P < .05). Conclusion: Our results showed that claudin-2 and renalase are associated with renal glomerular and tubular dysfunction and may play discrete roles in the pathogenesis of hypertension. We believe that these potential roles warrant further investigation.